Labeling Theory On the Legal Expression of Police Clearance Certificate - Ahmad Yulianto; Athari Farhani (STAATSRECHT: Indonesian Constitutional Law Journal, 2021)
Through state-owned equipment, the police are empowered to issue a Police Clearance Certificate (SKCK). However, SKCK cannot label someone if someone is evil or not. Whereas written legal norms are characterized by legal certainty, in other words, law without certainty values will lose its meaning because it can no longer be used as a code of conduct for everyone. By reviewing references or literature related to criminal acts, prevention of crime, legal certainty and authority. SKCK is a preventive action carried out by the police institution as the State institution that has the authority over security and order. The responsibility for crime prevention is carried out by the National Police and the public by carrying out pre-emptive and preventive tasks, namely making community members obey and obey the law. Polri is responsible for approximately 20% of activities while 80% of other activities are the responsibility of the community which consists of various elements. The most important thing is that the label of criminal not criminal is the authority of the court. So that SKCK is not based on crime prevention but is based on the concept of labeling.